Aging-induced multi-scale study on the interfacial adhesion mechanism of steel slag and RAP recycled asphalt mixtures - Yaodong Zhang; Yanan Cui; Shun Guo; Zhiyong Li (PLoS ONE, 2026)
To investigate the interfacial adhesion mechanism of steel slag and reclaimed asphalt pavement (RAP) dual solid waste recycled asphalt mixtures under aging conditions, the chemical and mineral properties of three aggregates (basalt, steel slag, and RAP) were characterized using XRF, XRD, and SEM-EDS. Interfacial adhesion behavior between asphalt and aggregates was studied through contact angle tests, AFM, and pull-off tests, and the evolution of interfacial properties during secondary aging of reclaimed asphalt was analyzed. The results show that Cl and S elements detected in the residual aged asphalt film on RAP aggregates represent the chemical imprint of the service environment. Chemical bonding occurs between steel slag and asphalt, forming a reaction transition layer, while basalt is dominated by physical adsorption with a clear and dense interface. Although the adhesion work of steel slag (69.12 mJ/m²) is slightly lower than that of basalt (71.01 mJ/m²), its pull-off strength (2.48 MPa) is higher due to mechanical interlocking from its rough and porous surface, revealing a synergistic enhancement mechanism. During reclaimed asphalt re-aging, functional group indices and micromorphology exhibit regular evolution, with 30h as the critical threshold for performance degradation. Adhesion work, AFM adhesion force, and pull-off strength show consistent positive correlations (R² = 0.92 and 0.89), forming a multi-scale interfacial performance evaluation system from thermodynamics to macro-mechanics.